Transdisciplinary Research Bridges the Gap between Science and Pastoral Services - Rampisela, Dorothea Agnes (Sekolah Tinggi Theologia Jaffray, 2020)
The flow of globalization has been unstoppable into most of the countries including Indonesia with this rapid transformation, the response must be integrated and comprehensive, involving all stakeholders from global governments, the public and private sectors to academics and the wider community. In this era, churches should unite in response to a changing context. Facing these challenges, teaching in universities and colleges is also demanded to change, including in producing quality scholars for future generations. What about Christian teaching and education? To what extent is it necessary or able to keep up with this global change? Is the role of theology or church school graduates still or will be increasingly needed? Transdisciplinary Action as new research policy is considered to be one of solution. The argumentative theory is used to verify whether transdisciplinary research is applicable and in line with Christian/ pastoral education and whether the transdisciplinary approachable to bridge the gap of science and the church service. This argument concluded several reasons and evidence that transdisciplinary research will improve the quality of pastoral service so that it bridges science to transform into quality service.Arus globalisasi tidak dapat dicegah masuk ke hampir semua negara termasuk Indonesia. Dengan perubahan yang sangat cepat ini respons haruslah terpadu dan komprehensif, meliputi semua stakeholder mulai dari pemerintahan global, sektor publik dan swasta, akademisi dan komunitas masyarakat luas. Dalam era seperti ini, gereja harus bersatu dalam merespons konteks perubahan. Dalam mengahdapi tantangan ini, pembelajaran di perguruan tinggi juga diharapkan ikut berubah termasuk dalam menghasilkan sarjana berkualitas untuk generasi masa depan. Bagaimana dengan Pendidikan dan Pengajaran Kristen? Sampai dimana hal ini masih dibutuhkan, dan apakah mampu bertahan dalam perubahan global ini? Apakah peran lulusan sekolah teologi atau gereja masih akan tetap semakin dibutuhkan? Aksi transdisiplinari sebagai arah penelititan terbaru dipertimbangkan sebagai salah satu solusi yang dapat dimanfaatkan. Teori argumentasi digunakan sebagai metode penelitian untuk membuktikan apakah penelitian transdisiplinari dapat diaplikasikan, dan sejalan dengan Pendidikan Kristen dan apakah pendekatan transdisiplin dapat menjembatani kesenjanganantara teori pengetahuan dan pelayanan gereja. Hasilnya menunjukkan bahwa ada beberapa alasan kuat serta bukti bahwa penelitian transdisiplin dapat meningkatkan mutu layanan gereja sehingga dianggap mampu menjembatani ilmu pengetahuan dan mentransformasikan menjadi layanan bermutu.